Community-based interventions to reduce dental caries among 24-month old children: a pilot study of a field trial - Marzie Deghatipour; Zahra Ghorbani; Amir Hossein Mokhlesi; Shahla Ghanbari; Mahshid Namdari (BMC, 2021)
Abstract Background Early childhood caries (ECC) is the most common dental disease among children worldwide, leading to many difficulties on child's growth. As WHO mentioned, educational interventions in addition to interprofessional collaboration are needed to achieve proper ECC prevention. In present study we've aimed to evaluate the effectiveness of some oral health promotion interventions to reduce dental caries among 24-month old children. Methods A field trial study was conducted amongst 439 mothers from pregnancy up to 24 months after delivery in Public Health Centers in Varamin, Tehran, Iran. Participants were allocated to intervention (n = 239) and control groups (n = 200). Demographic, socioeconomic status and dental care behavior data were collected using a questionnaire. The content of our study intervention consisted of nutritional and behavioral oral health-related messages. Mothers received messages via either of four methods (A: comprehensive method including all other methods together (n = 74), B: group discussion by dentists (n = 59), C: face to face education by primary health care providers (n = 53), and D: social network (n = 53). The control group received routine maternal and oral health care. To assess the effectiveness of interventions on promoting children's oral health, the oral health-related behaviors data, the number of decayed teeth (d), and being caries free at the age of two were considered. Results Among the 436 examined children, with a mean age of 23.7 months, 48.2% were male. The frequency of using finger toothbrush increased from 53.4% to 89.8% in all intervention groups. The mean (SD) of decayed teeth at 24 months in intervention and control group were 0.36 (0.93) and 1.61 (2.61), respectively. All the four intervention groups, except social network, had more chance of being caries free compared to control group (P value < 0.05). Analysis showed that children in comprehensive intervention group had a higher chance of being caries free compared to all other groups, after adjustment for covariates. Conclusions Performing oral health interventions could help the prevention of dental caries in newborn children. Also, using a combination of different methods of sending messages can have the best results in promoting oral health.